Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/md.0000000000021109
|View full text |Cite
|
Sign up to set email alerts
|

Primary ovarian carcinoid

Abstract: Introduction: Carcinoid tumor is one of the most frequent neuroendocrine tumors, and the majority of which are usually observed in the lungs and gastrointestinal tract. The prevalence of ovarian carcinoids is merely 0.1% in ovarian neoplasms and 1% in carcinoid tumors. We described 2 rare cases in our hospital of primary ovarian carcinoid (POC), causing carcinoid syndrome (CS) of the diarrhea, constipation, and carcinoid heart disease. Besides, we also reviewed related literatures about its origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Primary ovarian carcinoids account for only 0.1% of all ovarian neoplasms. [1,4] They are the most common primary neuroendocrine tumors in the genital tract. [5] The cause of primary ovarian carcinoids is unclear, but it originates from germ cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Primary ovarian carcinoids account for only 0.1% of all ovarian neoplasms. [1,4] They are the most common primary neuroendocrine tumors in the genital tract. [5] The cause of primary ovarian carcinoids is unclear, but it originates from germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] The age at diagnosis varies from 14 to 83 years, and peri- and postmenopausal women are the most affected. [1] Patients with primary ovarian carcinoids may present with no or nonspecific symptoms. Georgescu et al [7] analyzed 99 cases of primary ovarian carcinoids, described in 68 published articles and found that approximately 70% of the patients were symptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations